Technological innovation in policing and crime prevention: Practitioner perspectives from London - Laufs, Julian (International journal of police science & management, 2022)
Digital technology now plays a critical role in policing and security management, with policing apps, drones and body-worn cameras potentially being game-changers. Adoption of such technologies is, however, not straightforward and depends upon the buy-in of senior management teams and users. This study examines what obstacles practitioners face in the procurement, deployment and use of crime prevention and detection technologies. The issue is explored through a number of expert interviews conducted with practitioners in London between August 2019 and March 2020. This work expands previous, more theoretical, literature on the topic by adding a practical perspective and advances the understanding of issues faced in innovation processes and their management. We identified a variety of issues and obstacles to technological innovation for policing. These include the deployment of new systems at the cost of old ones, lack of financial and political support, issues in public–private partnerships, and public acceptability. Although individual practitioners may have the expertise and willingness to unleash the full potential of surveillance and crime-reduction technologies, they are usually restrained by institutional rules or, in some cases, inefficiencies. In terms of the latter, this study especially highlights the negative impact of a lack of technical interoperability of different systems, missing inter- and intra-agency communication, and unclear guidelines and procedures.